2019
DOI: 10.3389/fneur.2019.00528
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy and Neurodevelopmental Outcomes in Children With Etiologically Diagnosed Central Nervous System Infections: A Retrospective Cohort Study

Abstract: Background: Central nervous system (CNS) infection in childhood can lead to neurological sequelae, including epilepsy, and neurodevelopmental disorders, such as attention-deficit/hyperactivity disorder (ADHD) and autism spectrum disorder (ASD). This study investigated the association of etiologically diagnosed childhood brain infections with the subsequent risks of epilepsy and neurodevelopmental disorders. Objectives: We retrospectively analyzed the data of children aged <18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…The highest risk was conferred by central nervous system infections. A Taiwanese study 28 showed that systematic infection was an independent risk factor for epileptic seizures, conferring a 10.7-fold higher risk compared with the control group. In addition, human herpesvirus 6 (HHV-6), 29 Epstein-Barr virus (EBV), 29,30 respiratory syncytial virus infections, 31 and urinary tract infections 32 could increase epilepsy risk.…”
Section: Infectious Diseases and Epilepsymentioning
confidence: 99%
“…The highest risk was conferred by central nervous system infections. A Taiwanese study 28 showed that systematic infection was an independent risk factor for epileptic seizures, conferring a 10.7-fold higher risk compared with the control group. In addition, human herpesvirus 6 (HHV-6), 29 Epstein-Barr virus (EBV), 29,30 respiratory syncytial virus infections, 31 and urinary tract infections 32 could increase epilepsy risk.…”
Section: Infectious Diseases and Epilepsymentioning
confidence: 99%
“…Neurodevelopmental disorders (NDDs)[ 1 ] are a group of conditions that interfere with the central nervous system (CNS) development at an early age. Developmental brain dysfunction causes later neuropsychiatric problems that persist into adulthood, including the attention-deficit/hyperactivity disorder (ADHD), autism spectrum disorder (ASD), learning disabilities, and intellectual disability[ 2 ]. Numerous epidemiological reports[ 3 ] suggest an association between NDDs and prenatal exposure to viral pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of epilepsy increased by 78% due to infection (HR=1.78, 95% CI 1.73–1.83), with central nervous system infection showing the highest risk (HR=4.97, 95% CI 4.42–5.59). A study performed in Taiwan 29 indicated that central nervous system infection is an independent risk factor for epilepsy, increasing its odds by 10.7 times versus the control group. Furthermore, when infection-related epilepsy in children is not well cured, the in-hospital mortality rate could reach 16%.…”
Section: Discussionmentioning
confidence: 99%
“…24 Besides, genetic mutation is also one of the pathogenetic factors of epilepsy and mental/developmental disorders, with ion channel and synapse related genes being most commonly mutated. [25][26][27] Infectious Diseases and Epilepsy 29 indicated that central nervous system infection is an independent risk factor for epilepsy, increasing its odds by 10.7 times versus the control group. Furthermore, when infection-related epilepsy in children is not well cured, the in-hospital mortality rate could reach 16%.…”
Section: Neurodevelopmental Disorders and Epilepsymentioning
confidence: 99%